Regulation of brain metabolism by peripheral nutritional signals: the role of blood-brain barrier in health and disease - Dianhui ZHANG; Zhenni GUO; Yi YANG; Junlei CHANG (KeAi Communications Co., Ltd., 2022)
The blood-brain barrier (BBB) prevents unregulated substance exchange between the central nervous system and the blood, while providing highly regulated transport of nutrients and tonic factors essential to brain metabolism. A group of carriers, transporters, and receptors is utilized by endothelial cells of the BBB to aid the influx and efflux of nutrients and metabolic wastes, and their function is subject to changes during metabolic disorders such as diabetes mellitus and obesity. This regulated barrier function of BBB is essential for maintaining the normal metabolism of the brain and transduction of metabolic signals from the periphery. As such, disruption of the BBB nutrient/hormone transport system has been proposed to be major contributors of many neurological diseases.